Food Handler Behavioral Factors That Influence Food Sanitation Hygiene Requirements in Restaurants in Sinonsayang District - Agnes T. Watung; Katiandagho, Dismo; Donny Makalalag; Anselmus Kabuhung (Jurnal Kesehatan Cendikia Jenius, 2025)
Food sanitation hygiene is a preventive effort that focuses on activities and actions that are necessary to free food and drink from all dangers that could interfere. The results of the initial survey conducted show that it still exists food handlers who process food do not use aprons, head coverings, sarongs hands, dressed sloppy and food handlers do not carry out health checks every month. The aim of the research is to determine the behavioral factors of food handlers which is related to food sanitation hygiene in restaurants in Sinonsayang District. The type of research is Cross-sectional, the independent variables are knowledge, attitudes and actions and the dependent variable is the hygiene and sanitation requirements of the restaurant. The sample in this study was 7 restaurants with 24 food handler respondents. The instruments in this research are questionnaires and observation sheets. The research data were analyzed univariately and bivariately which were analyzed using correlation tests. The research results prove that there is a meaningful relationship between knowledge and values p = 0.034, the attitude that gets the value p = 0.010 and actions towards hygiene and sanitation requirements for restaurants in Sinonsayang District, which received a score p = 0.020. The conclusion is that there is a significant relationship between the knowledge, attitudes and actions of food handlers towards the sanitation and hygiene requirements of restaurants in Sinonsayang District. It is recommended that food handlers maintain personal hygiene when handling food, so as not to become a medium for transmitting disease through food.